Multi-cores for Signal Processing; Using Instruction Set Simulation to explore performance of LTE (Long Term Evolution) applications - Ahmed, Muhammad Ismail (My University, 2009)
Increasing multimedia demands and mobile broadband has forced the cellular operators to adapt radio technologies that meet requirements of next generation (mobile TV, real time audio/video etc.). LTE (Long Term Evolution) is the radio technology that already meets most of 4G (Fourth generation) requirements. But to exploit higher data rates offered by LTE, powerful processing engines are required at mobile base stations. Multi-cores due to low power consumption and high performance are considered a natural choice however novelty of multi-cores combined with evolving LTE application software has forced the developers to use Instruction Set Simulators, which allows testing the application software on hardware that does not exist or is in short supply. Simics is one such simulation technology with special multi-core development tools, capable of simulating dozens of cores at adequate levels of speed and accuracy. An existing single core Simics model of the target hardware is modified and a 14 core hardware model is created, to accommodate the parallelized (14 part) LTE application. Simics helped in constructing the target multi-core hardware with relative ease, which consequently enabled the development of application software for it.
Keywords: Datorteknik; Computer Engineering